2021
DOI: 10.21315/eimj2021.13.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Mental Health Status and Coping Strategies in Their Quarantine Period During COVID-19 Pandemic in Universiti Putra Malaysia

Abstract: Movement control order (MCO) was enforced by the Malaysian government on 18th March 2020 due to sudden increase in the cumulative number of COVID-19 cases. University students, including medical students, were among the group of the population which were significantly affected. This study was conducted among medical students in Universiti Putra Malaysia (UPM) to compare the mental health status and coping strategies, between gender and phase of the clinical study related to their quarantine status between 18th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A number of techniques exist to help researchers' mental health and coping strategies. Physical activities such as exercise, playing sport, jogging or brisk walking, and meditation, as well as mentor-mentee/buddy programs between supervisors and students, are a few of them (14).…”
Section: Solution and Opportunitiesmentioning
confidence: 99%
“…A number of techniques exist to help researchers' mental health and coping strategies. Physical activities such as exercise, playing sport, jogging or brisk walking, and meditation, as well as mentor-mentee/buddy programs between supervisors and students, are a few of them (14).…”
Section: Solution and Opportunitiesmentioning
confidence: 99%
“…Currently, there are a handful of studies looking into self-esteem [10,11], self-efficacy [21,22] and coping skills [23,24] with anxiety in different contexts and population groups. However, to the author's current knowledge, there are very few to no published studies exploring the interrelationship between all these traits, together with anxiety among medical students, particularly in the Malaysian setting, during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Covid-19, according to O' Byrne et al, will impact the educational integrity of medical pro-grams. 7,9,10,11,12,13 Many universities have canceled the clinical clerkship to minimize exposure to Covid-19. 14,15 This delays clinical posting and affects academic records.…”
Section: Introductionmentioning
confidence: 99%
“…A study done among medical students at Universiti Putra Malaysia reported that mental health among clinical students is significantly affected among quarantined clinical students compared to preclinical students during the pandemic. 9 Therefore, the study aims to assess UNIMAS medical students' mental health during the Covid-19 pandemic. In addition, this research is aimed to discover the factors that influence mental health and the coping mechanism to improve mental health problems.…”
Section: Introductionmentioning
confidence: 99%